Bay lodyans : Haitian popular film culture - Accilien, Cécile, 1973- (Albany : State University of New York Press, 2023)
"Considers how popular Haitian films not only provide entertainment but also help audiences in Haiti and the diaspora think through daily challenges"--
Introduction: Dèyè mòn gen mòn -- Searching for home : im/migration, deportation, and exile in Dyaspora $100, Kidnappings, and Deported ; Conversations about home and deportation with Rachèle Magloire -- Language, class, and identity : Pale franse pa vle di lespri pou sa ; Conversations about language with Jacquil Constant and Rachelle Salnave -- Representations of religion : Protestant views of Vodou in Madan Pastè a (1 & 2) and Matlòt (1, 2, & 3) ; Conversations about religion with Mario LaMothe and Anne François -- Gender and heteronormative sexuality : Cousines, Facebook Player, and Gason ; Conversations about gender with Rachèle Magloire and Carole Demesmin -- Navigating same-sex desire : Fanm and Jere m Cheri ; Conversations about same-sex desire with Mario LaMothe and Anne François -- Conclusion: Ayiti Nou Vle a (The Haiti we want) : creating new narratives for a new Haiti.
Includes bibliographical references and index.
Description based on print version record.
JSTOR
Keywords: Motion pictures -- Haiti; Haitians in motion pictures; Motion picture producers and directors -- Haiti; Motion picture industry -- Haiti; Haitian diaspora; Cinéma -- Haïti.; Producteurs et réalisateurs de cinéma -- Haïti.; Cinéma -- Industrie -- Haïti.; Haïtiens -- Pays étrangers.; PERFORMING ARTS / Film & Video / History & Criticism; Haitian diaspora; Motion picture industry; Motion picture producers and directors; Motion pictures; Haiti